Pengaruh Sales Promotion pada Keputusan Pemilihan Sebuah Wedding Organizer Studi Kasus: Segmentasi Kalangan Atas di Jakarta - Ina Melati (Bina Nusantara University, 2014)
Sales promotion is almost always used as a marketing tool that is potential to increase sales of a product. Nevertheless, the reality is totally different because of differences in segmentation and characteristics of the product or service that will be sold should be a concern for marketers. It turns out that not all segmentations will be loyal to a product/service because of sales promotion, take one example: when upper class customers in choosing a wedding organizer. With etnography study and in depth interview, consumer insight is obtained about their opinion on sales promotion.